Tobacco-smoking-related differential DNA methylation: 27K discovery and replication - Breitling, Lutz Philipp; Yang, Rongxi; Korn, Bernhard; Burwinkel, Barbara; Brenner, Hermann (The American journal of human genetics, 2011)
Tobacco smoking is responsible for substantial morbidity and mortality worldwide, in particular through cardiovascular, pulmonary, and malignant pathology. CpG methylation might plausibly play a role in a variety of smoking-related phenomena, as suggested by candidate gene promoter or global methylation studies. Arrays allowing hypothesis-free searches on a scale resembling genome-wide studies of SNPs have become available only very recently. Methylation extents in peripheral-blood DNA were assessed at 27,578 sites in more than 14,000 gene promoter regions in 177 current smokers, former smokers, and those who had never smoked, with the use of the Illumina HumanMethylation 27K BeadChip. This revealed a single locus, cg03636183, located in F2RL3, with genome-wide significance for lower methylation in smokers (p = 2.68 × 10−31). This was similarly significant in 316 independent replication samples analyzed by mass spectrometry and Sequenom EpiTyper (p = 6.33 × 10−34). Our results, which were based on a rigorous replication approach, show that the gene coding for a potential drug target of cardiovascular importance features altered methylation patterns in smokers. To date, this gene had not attracted attention in the literature on smoking.
Gesehen am 22.06.2022